PENGARUH DISIPLIN BELAJAR DAN LINGKUNGAN TEMAN SEBAYA TERHADAP PRESTASI BELAJAR MAHASISWA AKUNTANSI STIE NASIONAL BANJARMASIN - Ruslinda Agustina; Masrifani -; Anita Nopiani (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2017)
Abstract,This study aims to provide empirical evidence of the influence of the discipline of learning and the environment of peers against the achievement of accounting student study at STIENAS Banjarmasin.Population in this research is student of accounting year of year 2013 active in 2016 school year amounted to 129 student. Primary data by distributing questionnaires to respondents assisted with SPSS statistical test tool version 16.00 for windows.The results of this study indicate that the variable of learning discipline has no effect on student achievement of accountancy STIENAS Banjarmasin and peer environmental variables have an effect on student achievement of accountancy STIENAS Banjarmasin and simultaneously variable of learning discipline and peer environment have an effect on to learning achievement. Student accounting STIENAS banjarmasin. Limitations in this study, there are only variable learning discipline and peer environment, is expected to further research can add other variables in research such as learning motivation variables, attitudes and interest in learning, which can affect student achievement. Then can expand the sample and research area is not limited to one object only, so that the results of research can be more varied and accurate.